Learning the Yellow Book in Al-Fitroh Jejeran Boarding School, Wonokromo Pleret Bantul: Study of Learning Materials in Philosophical Perspective - Mujahid, Mujahid (Jurnal Pendidikan Agama Islam, 2021)
Many studies on boarding school have been carried out before by researchers. But most of these studies are more descriptive by describing what happened in the boarding. While studies about boarding school analyzed with philosophical theory are still rarely conducted. The subjects of this study were caregivers and some students who were selected purposively. The data collection uses observation, interview and documentation. This paper aims to reveal the philosophical perspective of the learning materials of the Yellow Book in al-Fitroh Jejeran Boarding school, Wonokromo Pleret Bantul. The philosophical framework used as a reference for the analysis of this study is the Religious-Conservative tradition (al-Diniy al-muhafidz). Religious -Rational (al-Dini al-' Aqliy) and Pragmatic-Instrumental (al-Darai'i) traditions. The results showed that philosophically learning the Yellow Book in that boarding school uses religious-conservative tradition (al-Diniy al-muhafidz). The source of the material taught refers to the yellow books produced by scholars in the Middle Ages. The reason Kyai refers in the classical books because the books were written by salafiyyin scholars closer to its existence with the Prophet, to allow the truth is more assured. According to his beliefs getting closer to the existence of the prophet, the value of truth is more authentic. While the Religious-Rational School (al-Dini al-'Aqliy) has not got an adequate place in the Boarding School. The existence of general science is not given to students so that the students are not affected by outside influences that will slowly erode and keep students away from religious sciences. While the instrumental pragmatic tradition (al-Darai'i) which is characterized by accommodating a variety of tangible sciences related to the direct needs of humans, both spiritual needs and material needs, must be recognized not all can be organized by the boarding school completely.